Collected papers v. phenomenology and the social sciences - Schutz, Alfred; Embree, Lester; SpringerLink (Online service). (Dordrecht Springer Netherlands, 2011)
This volume begins with Schutz's sketch of how Husserl influenced him. It shows how phenomenological theory of the social sciences differs from positivistic approaches, and presents Schutz's theory of relevances--a key feature of his own phenomenology of the social world. It contains exchanges between Schutz and Eric Voegelin, Felix Kaufmann, Aron Gurwitsch, and Talcott Parsons, and presents, for the first time, Schutz's incisive criticisms of T.S. Eliot's theory of culture.
Editorial Introduction; Husserl and His Influence on Me; Choice and the Social Sciences; The Theory of Social Action: Correspondence between Alfred Schutz and Talcott Parsons; Reflections on the Problem of Relevance; Outlines on Relevance and Action; T. S. Eliot's Theory of Culture; Letters of Schutz to Felix Kaufmann; Letters of Schutz to Gurwitsch; Letters of Schutz to Voegelin.
Electronic reproduction.
Keywords: Phenomenology; Social sciences -- Philosophy; Electronic books